Combinatorics of Second Derivative: Graphical Proof of Glaisher-Crofton Identity - Pawel Blasiak; Gérard H. E. Duchamp; Karol A. Penson (Advances in Mathematical Physics)
We give a purely combinatorial proof of the Glaisher-Crofton identity which is derived from the analysis of discrete structures generated by the iterated action of the second derivative. The argument illustrates the utility of symbolic and generating function methodology of modern enumerative combinatorics. The paper is meant for nonspecialists as a gentle introduction to the field of graphical calculus and its applications in computational problems.